Serum Raman spectroscopy: Prognostic applications in oral cancers. Issue 5 (15th March 2023) - Saha, Panchali; Sawant, Sharada; Deshmukh, Atul; Hole, Arti; Murali Krishna, C.
Abstract: Background: Loco‐regional recurrences attributable to field cancerization and minimal residual cancer, remain prime causes of mortality in oral cancer (OC) subjects. The current study evaluates potential of serum Raman spectroscopy (SRS) to identify recurrence‐prone OC subjects. Methods: Raman spectra of serum from eight healthy subjects (H) and 57 OC subjects (with‐recurrence [R], without‐recurrence [NR], and with suspicious‐lesions [S]), before (BS) and after (AS) surgical excision of tumor were recorded. OC subjects were followed‐up for 7‐years. Results: DNA and protein alterations were observed in AS sera of all groups. 4‐, 3‐, and 2‐model multivariate analyses were used to stratify BS and AS groups. H spectra were 100% distinguishable from all other groups. AS, R and NR were distinguished with high accuracy (84%) in all models. No stratification (~50%) was observed BS. Conclusion: SRS shows potential to identify recurrence prone subjects, post‐surgery, using serum collected as early as 1 week after surgery.